Exogenous Arachidonate Restores the Dimethoate‐Induced Inhibition of Steroidogenesis in Rat Interstitial Cells - Astiz, Mariana (2012)
The present work studies the potential restorative effect of polyunsaturated fatty acids (PUFAs, 5μM/24 hs) on the dimethoate (DMT)-induced inhibition of testosterone biosynthesis in Leydig cells isolated from rat testes. Various fatty acids (FAs) from the n-6 (18:2, 20:3, 20:4, 22:4 and 22:5) and n-3 (18.3, 20:5, 22:5, 22:6) series were assayed in Leydig cells, alone (as delipidated BSA complexes) and in combination with DMT (1 ppm). The n-6 FAs stimulated lipid peroxidation (LPO) and inhibited the activities of steroidogenic enzymes (3beta- and 17beta-hydroysteroid dehydrogenases). The n-3 FAs exerted an anti-oxidant effect, decreasing the production of thiobarbituric-acid reactive substances (TBARS) and inhibiting phospholipase A2 activity. 20:4n-6 (ARA), completely and 20:3n-6 partially, normalized the biosynthesis of testosterone in DMT-treated cultures, increasing ARA content inside the mitochondria, whereas the other FAs assayed failed to restore androgenesis. COX-2 protein and prostaglandin F2alfa and E2 production were stimulated by 20:3n-6, 20:4n-6, 18:3n-3 and 20:5 n-3. COX-2 protein decreased upon addition of 22:5n-3 and 22:6n-3. StAR protein was increased by 20:4n-6 and partially by 20:3n-6, likely due to its metabolic conversion into ARA. Both FAs increased the mitochondrial cholesterol pool available for testosterone biosynthesis. The rate of androgenesis is likely the result of various regulatory factors acting concomitantly on the physiology of Leydig cells.